Relationship between Pain Levels and the Independence of Elderly People with Rheumatoid Arthritis in UPTD Puskesmas Mengwi II - Dewi, Dewa Ayu Rai Utami; Martini, Ni Made Dwi Ayu; Purwaningsih, Ni Komang; Sutresna, I Nyoman (Muhammadiyah Journal of Geriatric, 2024)
Background: The elderly are individuals aged ≥60 years who will experience functional changes in their body systems, including the musculoskeletal system, and put them at high risk of suffering rheumatoid arthritis. This disease causes joint pain and often affects the elderly's ability to carry out daily activities, thus having an impact on the elderly's level of independence. Purposes: This study aimed to determine the relationship between pain levels and the independence of elderly people with rheumatoid arthritis in UPTD Puskesmas Mengwi II. Methods: This research is a quantitative study that used a correlational design and a cross-sectional approach. The sample was 67 elderly people with rheumatoid arthritis who were selected by the Purposive Sampling technique. Data were collected using the Numerical Rating Scale and Barthel Index, which were analyzed using the Spearman Rank test. Result: The results showed that the average score of pain level in elderly people with rheumatoid arthritis was on a scale of 4 (moderate pain), with an average independence score of 75.37 (mild dependence). The results of bivariate analysis showed that there was a relationship between pain level and the independence of elderly people with rheumatoid arthritis (p=0.000; r= -0.591). Conclusion: the pain level of rheumatoid arthritis impacts the elderly’s activities, so the nursing services can optimize pain management so that elderly people will not experience problems in carrying out their daily activities independently.